Does Postural Awareness Contribute to Exercise-Induced Improvements in Neck Pain Intensity? A Secondary Analysis of a Randomized Controlled Trial Evaluating Tai Chi and Neck Exercises. Issue 16 (15th August 2017) - Lauche, Romy; Wayne, Peter M.; Fehr, Johannes; Stumpe, Christoph; Dobos, Gustav; Cramer, Holger
Abstract : Study Design: Secondary analysis of a randomized controlled trial. Objective: This secondary analysis aims to examine associations of improvement of chronic neck pain with patients' and intervention-related characteristics. Summary of Background Data: Previous research has found that Tai Chi and neck exercises significantly improved chronic nonspecific neck pain; however, the factors for treatment success remain unclear. Methods: Subjects with chronic nonspecific neck pain were randomly assigned to 12 weeks of group Tai Chi or conventional neck exercises, and they attended 12 weekly sessions of 60 to 90 minutes. The interventions included exercises to improve body awareness, that is, interoceptive and postural awareness. A linear forward stepwise regression analysis was conducted to examine associations with improvements in neck pain intensity. Potential predictor variables included baseline pain, age, sex, the type of intervention, attendance rate and home practice duration, and changes in psychological well-being, perceived stress, and postural and interoceptive awareness during the study. Results: Overall 75 patients were randomized into Tai Chi or conventional exercises, with the majority being women (78.7%). Participants reported an average pain intensity of 50.7 ± 20.4 mm visual analog scale at baseline, and the average reduction of pain intensity in both groups was 21.4 ± 21.3 mm visual analog scale. Regression analysis revealed that reductions in pain intensity from baseline to 12 weeks were predicted by higher pain intensity at baseline ( r 2  = 0.226, P  < 0.001), a decrease in anxiety ( r 2  = 0.102, P  = 0.001), and an increase in postural awareness ( r 2  = 0.078, P  = 0.0033), explaining a total of 40.6% of variance. Conclusion: Neck pain improvement was significantly associated with changes in postural awareness in subject with chronic nonspecific neck pain independent of treatment characteristics. Training of postural awareness might be an important mechanism of action of different exercise-based interventions for chronic neck pain. Level of Evidence: N /A Abstract : Supplemental Digital Content is available in the text